Fast inter prediction algorithm applied in quality SVC - WANG Da-yong1; SHU Jian2 (Tongxin xuebao)
Based on the characteristics of quality scalable video coding,a fast inter encoding algorithm was proposed on the enhancement layer for the medium-grain quality scalability（MGS）.Firstly,based on the base layer macroblock mode and rate-distortion,the order of the coding mode for the current macro block was proposed.Then based on the encode structure,the correlation between layers,and the spatial correlation,desicions for the Direct coding mode,layer mode,and adjacent mode were proposed,respectively.Finally,the macroblocks were encoded in the order predicted,with the proposed three decisions to improve on the coding speed by early termination.The experimental results show that the computational complexity of the algorithm is reduced by 68% on the average compared to that of the standard method,with only negligible coding loss and bit-rate increase.